Arapiraca no estado de Alagoas : história, discurso e (arte)fatos na invenção da terra do fumo – (1950-1990) - Santos, Daniel Alves dos (2020)
Arapiraca, in the interior of the state of Alagoas, is a city with great importance in the scenario of the economy, politics and state culture. From 1950, this city suffered an industrial manufacturing cycle in which tobacco was the main raw material of the industries that settled in the city and acted in the urban transformation, as well as the rural space. The tobacco processing sector is, until the present day, regarded as the main contributing factor for Arapiraca to become known for its relationship with the tobacco culture. Thus, this dissertation analyzes how Arapiraca's visibility and sayability was constituted from his experience with the tobacco culture and his invention as Land of Tobacco. For this, we use a diversity of sources that have served us to build the corpus of research. Journalistic materials, local legislative documents, photographs, audio and video interviews, official symbols such as the anthem and flag of Arapiraca, music, monuments of local architecture, all analyzed without hierarchy, with the same importance, were used. As a starting point, we believe that for the invention of Arapiraca, with smoke as the guiding element of this invention, it was necessary to create a series of discursive and non-discursive elements for the elaboration of a memory intertwining the groups that participated in this process, giving meaning to a whole symbolism in the regional elaboration as a division creating the Arapiraca has a tobacco’s land give meaning to regional identity in opposition to the sugar's cane comprehensive identity of Alagoas. The result of what the sources helped us to build is divided into the three chapters presented in this dissertation. The first of them brings the process of historical and regional development of Arapiraca and the links that put this city in a prominent position in the state of Alagoas. In the second chapter, we seek to understand the conflicting relations of elaborating a sayability and visibility in relation to Land of Tobacco, as well as to highlight the participation of several characters in this elaboration, being these, entrepreneurs, politicians, fair singers and women smoke destaladeiras, all acting in the construction of a local imaginary. In the third chapter, we see how the historical conditions gave rise to a series of elements, among them a pictorial discourse that invented the tobacco’s land identity. Plastic arts, architecture and music in the elaboration of an arapiraquense memory. It is concluded that Arapiraca is the result of a series of economic, social and cultural factors, all related composing a same discourse of elaboration of this city